2014
DOI: 10.1503/cjs.006211
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to adjuvant endocrine therapy in estrogen receptor–positive breast cancer patients with regular follow-up

Abstract: Background: Adjuvant hormonal therapy is crucial in the treatment of estrogen receptor-positive breast cancer. The nonadherence rate to hormonal treatment is reported to be as high as 60%. The goal of this study was to evaluate the factors evoked by the patients as well as the demographic and disease-related factors that could be associated with nonadherence to adjuvant hormonal therapy.Methods: All consecutive patients treated for an estrogen receptor-positive breast cancer who showed up for regular follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 34 publications
6
44
1
1
Order By: Relevance
“…As noted in other studies [13,15,16,18,23], the present study found that the side effects attributed to anti-hormonal medications by survivors were the main barrier for non-adherence. Most side effects described were physical, but some survivors also reported psychological side effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As noted in other studies [13,15,16,18,23], the present study found that the side effects attributed to anti-hormonal medications by survivors were the main barrier for non-adherence. Most side effects described were physical, but some survivors also reported psychological side effects.…”
Section: Discussionsupporting
confidence: 82%
“…Intolerable side effects are the most common reason patients discontinue using anti-hormonal medication [13,1518]. Side effects vary by medication and can include weight gain, joint pain, hot flashes, headaches, fatigue [19], decreased libido, mild arthritis, vaginal discharge, abdominal bloating, and bone density loss [15].…”
Section: Introductionmentioning
confidence: 99%
“…(6, 52)(16, 53, 54) Psychological factors, such as beliefs, perception, education, source and quality of information, social support, have also been shown to contribute. (14, 16, 18, 55) Although a diagnosis of cancer and the fear of recurrence have been reported by patients as reasons for better adherence(56), higher cancer stage and, thus, higher risk of recurrence, has not been consistently associated with better adherence. (12) The patients’ inherent beliefs about the medicine and side effects also have an impact on adherence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of progression (or recurrence, hereafter FOP), defined as "fear that the illness will progress (…) or that it will recur" (p. 13), 1 is a prevalent concern among breast cancer patients. 2 While, to a certain degree, the fear that cancer might progress may function as a motivating factor that promotes healthy behavior or adherence, 3 excessive fear might function as an inhibitor. 4 As such, FOP has been the subject of empirical studies and systematic reviews, 5 and theoretical frameworks to understand FOP have been suggested.…”
Section: Introductionmentioning
confidence: 99%